Denied Investment: A Case of Community Member’s Attitudes towards Volunteering in Corporate Social Investment Initiatives - Muzindutsi, Paul-Francois (Journal of Economics and Behavioral Studies, 2015)
Companies use corporate social responsible investment (CSI) initiatives to contribute to the wellbeing of the society they operate in. South African companies continue to increase their involvement in CSI initiatives in the areas of education and training, capacity building, community development and health care. The impact of these initiatives can be extended, if community members, who are mostly the beneficiaries of these initiatives, are willing to work with companies through volunteering in CSI initiatives. This study used a combination of qualitative and quantitative research designs to assess the attitude of community towards volunteering on a CSI project. Interviews and survey questionnaire were used to collect data from households’ members who benefited from a CSI initiative of re-roofing houses in one of low income areas of South Africa. Qualitative analysis revealed that the CSI project provided skill which opened employment opportunities to community members who worked on the project. However, quantitative results showed that only 30% of participants were willing to volunteer on the CSI project. The majority of those who were not willing to volunteer on the CSI project were unemployed and did not have any skills; implying that volunteering on the CSI project could have provided them with some skills. Based on the investment model of volunteering, findings of this study showed that beneficiaries of the CSI initiative denied an investment opportunity due to their attitude towards volunteering. Hence, it was concluded that CSI initiatives could have a greater impact if community members are encouraged to participate in CSI initiatives as volunteers.